O psicólogo no terceiro setor: os sentidos do trabalho no enfrentamento à desigualdade social - Silva, Camila Young da (2011)
The objective of this study is to promote analyses regarding meanings relating to the professional activities of psychologists working within their institutional environment, with respect to teamwork and the population being cared for. The activities are performed in the third sector, and it aims to investigate aspects which try to understand actions when confronting social inequalities. It is a qualitative study, based on perspective assumptions of Social Critical Psychology developed by Vigotski and followers. Followers include studies developed by the Nucleus of Studies of the Dialetics within a framework using elements of Espinosa s philosophical ideas (particularly his reflections concerning the effectiveness of political-ethics). A semi-driven interview with the director, the social assistant and the psychologist was undertaken in two different institutions. The aim was to understand the level of work professionalism. One institution was organized by having its work structured with properly employed professionals while the other institution worked mainly with volunteers. From the reports produced, it was possible to construct meaning levels (belief systems), and, within this framework, consider motivations and emotional responses relating to the professionals working in the above quoted institutions. The analysis considered the political and managerial background of the third sector and the limits, possibilities and limitations of the psychologist considering the established public policies which regulates activities in a capitalist society. The results suggested that by confronting social inequalities, within the third sector, a situation of political weakness is observed, where ready-made practices prevails for dealing with day-to-day practices. Affection is perceived as solidarity practices and not as a result of policy action (or political determination). It is possible to perceive that psychologists´ actions are not performed as inter-disciplinary actions (weakening professional effectiveness). In this way, actions are considered necessary to include the social (subjective) context, and to find new ways to increase (with useful innovations) professional practices. It can be concluded with this study, that actions of the third sector (performed within known public policies), are being limited because of bureaucratic problems which arises as a result of political and personal interests (not supposed to be present, but which unfortunately exist)